The Effectiveness of Lavender Aromatherapy Technique on Pain Reduction of Post Caesarean Section Patients in Ajibarang Hospital - Haniyah, Siti; Setyawati, Martyarini Budi (Jurnal Keperawatan Soedirman, 2018)
ABSTRACTThe number of caesarean section birth in Indonesia were 22.8% or 921,000 out of 4,039,000 childbirth. The patients become conscious when the anesthetic effect disappears and they will feel pain in the incision area that makes them uncomfortable. One of the methods to reduce pain of Caesarean Section is lavender aromatherapy technique. The purpose of this study was to determine the effectiveness of lavender aromatherapy technique on pain reduction of caesarean section post-operative patients in Ajibarang hospital. This study was conducted by using a quasi-experimental design with pretest-posttest design. The samples were 22 respondents divided into two groups; 11 respondents received lavender aromatherapy treatment and 11 respondents were in the control group. Paired t test was used to describe pain scale differences in the control group and intervention. The results showed that there was a difference in the pain scale between lavender aromatherapy technique group and the control group with p value of 0.000. It can be concluded that lavender aromatherapy technique reduces pain in post-operative caesarian section patients.ABSTRAKAngka kejadian Caesarean section di Indonesia 921.000 dari 4.039.000 persalinan (22,8%) dari seluruh persalinan. Pasien akan mulai bergerak saat efek anastesi telah habis dan setelah itu mereka akan merasakan nyeri pada area pembedahan sehingga menimbulkan ketidaknyamanan. Salah satu metode untuk menangani Nyeri post Sectio C aesarea adalah dengan teknik aroma terapi lavender.Tujuan dari penelitian ini adalah untuk mengetahui efektifitas teknik aroma terapi lavender terhadap nyeri pada pasien post operasi Caesarean section di RSUD Ajibarang Desain penelitian ini adalah quasi eksperiment with pretest-posttest design dengan sampel 22 responden terbagi menjadi 2 kelompok, 11 responden mendapatkan aroma terapi lavender, dan 11 responden sebagai kelompok kontrol. Uji beda dua mean antar kelompok menggunakan uji Paired T test. Terdapat perbedaan skala nyeri antara kelompok aroma terapi lavender dengan kelompok kontrol p value 0,000. Kesimpulan dari penelitian ini adalah: terdapat pengaruh antara teknik Aroma Terapi Lavender terhadap penurunan nyeri Post SC.